Upper Bound Finite Element Limit Analysis of Pullout Characteristics of Normal-Stressed Circular Anchor Plate. (8th June 2022) - Luo, Yibo; Wei, Bin; Huang, Dongliang; Lv, Guoshun; Hu, Shihong
Abstract : In this paper, the pullout factor and failure mode of circular anchor plate at an inclined angle with the horizontal ground under the normal stress are studied with the method of the upper bound finite element limit analysis. The effects of soil cohesion, internal friction angle, anchor plate inclination angle, and embedded ratio on the pullout factor are investigated to reveal the evolution of fracture surface of the soil around anchor plate under limit state. It is noted that the analysis of variance is adopted to process a series of data related to pullout capacity for obtaining the expression of the anchor plate's pullout factor. The results show that the internal friction angle is the key factor determining the pullout characteristics of the anchor plate. Particularly, the effect of the inclination angle on pullout capacity is highly correlated to the internal friction angle. For φ = 0 °, failure zone around anchor plate is presented as localization plastic zone and pullout capacity is linearly related to soil cohesion. The effect of inclination angle on pullout resistance is less significant. For φ ≠ 0 °, the failure mode around the anchor plate is developing into full failure zone extending from both sides of anchor plate to ground. It is clearly noted that angle between the failure surface and horizontal line is greatly affected by the inclination of the anchor plate. Moreover, the effect of the inclination angle on pullout factor increases with increasing internal friction angle, which should be considered in the evaluation of the pullout bearing characteristics of the inclined circular anchor plate.